Digital Transparency and Consumer Awareness: Digital Platforms for Educating Consumers about Product Origins and Sustainability - Tolegenov, Bakyt; Rafif, Kevin; Rafi, Muhammad; Herawati, Rafidah; Abdullah, Asaduddin; Sari, Linda Karlina (AL-MUZARA'AH, 2024)
This paper investigates the role of digital transparency in enhancing consumer awareness of product origins and sustainability. As consumers increasingly seek to make informed, ethically aligned purchasing decisions, digital platforms - such as blockchain-enabled systems, mobile apps, and e-commerce sites - offer a medium for brands to communicate supply chain transparency. Through a comprehensive literature review, this article examines how transparency practices impact consumer trust, decision-making, and the adoption of sustainable products. Findings reveal that while digital platforms can significantly influence ethical consumption, their effectiveness depends on the clarity, accessibility, and perceived credibility of information presented. Key challenges, including greenwashing and information overload, can hinder transparency efforts, thereby reducing consumer trust. Additionally, stakeholder theory and the theory of planned behaviour provide insights into the ethical responsibilities of brands and the cognitive factors shaping consumer choices. Practical recommendations are offered, including the need for simplified, interactive transparency tools and collaboration with third-party certifiers to enhance authenticity. The study highlights the importance of evolving digital transparency practices to meet the ethical demands of modern consumers and suggests ways for future research to explore the impact of transparency across diverse consumer segments and regions.